STUDY OF STABILITY AND STORAGE CONDITIONS OF FITIROL TABLETS BASED ON IGPA OBTAINED FROM RICE FLOUR (ResearchJet Journal of Analysis and Inventions, 2021)
The results of experimental studies on stability studies and establishment of shelf life of "fitirol" tablets are presented. Tablets made according to the optimal composition and rational technology ensure the stability of their qualitative and quantitative indicators for 3 years and meet the requirements of GF XIV.